Evaluation of Public-Private Partnership (PPP) policies in service delivery access, quality, and accountability: A literature review - Nadia Putri Untiami; Siti Aisyah; Amanda Safitri; Riswandy Wasir (Indonesian Journal of Health Science, 2026)
Public-Private Partnership (PPP) has emerged as a strategic instrument to address fiscal and infrastructure constraints in achieving Universal Health Coverage (UHC) in Indonesia. However, its implementation effectiveness is often hindered by governance complexities and low transparency. This study aims to evaluate PPP policies in the healthcare sector, focusing on implementation dynamics, performance determinants, and policy improvement implications for access, quality, and accountability. This research utilizes a descriptive-analytical literature review method through systematic searches of Google Scholar, PubMed, BMC, and IJHPM databases for the period 2018–2025. The findings indicate that PPP significantly expands service access at primary and referral levels and fosters medical technology innovation. In Indonesia, the flexibility of BLUD status in regional hospitals supports Operational Cooperation (KSO), while at the primary level, private primary care facility (FKTP) integration strengthens basic service coverage. Nonetheless, major identified barriers include low contract transparency, information asymmetry, fragmented health information systems, and a shortage of competent medical personnel. Strengthening PPP governance requires more standardized regulations, rigorous independent oversight, and active public-interest-oriented contract management to ensure the sustainability of healthcare service quality and accountability.